Legal Services Support Centers and Rebellious Advocacy: A Case Study of the Immigrant Legal Resource Center - Bill Ong Hing (Washington University Journal of Law & Policy, 2008)
The purpose of this Essay is to provide a description and analysis of the ILRC’s work, with particular focus on its civic participation projects. While I provide a brief review of many ILRC programs, this Essay more fully describes ILRC’s work to build capacity among immigrants and refugees and the organizations that serve them to enhance the engagement and influence of newcomers in American civic life. That work includes work with immigrant service organizations to develop and implement grassroots campaigns to improve immigration laws, and the development and promotion of new models of service that transfer knowledge, skills and power to immigrants. By focusing on civic participation examples, the Essay describes projects that exemplify the program’s social change lawyering as it attempts to facilitate democratic participation by immigrants. In the process, methods are described in which ILRC staff attorneys go about doing this work in a rebellious, collaborative manner that simultaneously seeks to de-marginalize the individuals and groups with which they work. Thus, the aim of the Essay is to provide an insight into how the organization has gone about doing its business in this area, in hopes of gleaning lessons and approaches that other legal services and law school clinical programs can find useful.
Keywords: Clinical legal education; Collaborative law; Refugee legal assistance; Immigration Reform and Control Act of 1986; Community lawyering; Social change lawyering; ILRC; United States